Illicit activity and scarce natural resources in the supply chain: A literature review, framework, and research agenda. Issue 2 (13th February 2023) - Hilend, Rowan; Bell, John E.; Griffis, Stanley E.; Macdonald, John R.
Abstract: This article reviews extant multidisciplinary literature to uncover existing themes and directions in the knowledge of the overlap between natural resource scarcity and illicit supply chain activity. In doing so, the authors present a novel review of this nascent, complex, and multidisciplinary research area. This review has uncovered 127 articles that have not been synthesized or organized in a meaningful way with the supply chain literature. It extracts insights and develops a comprehensive process framework encompassing the following: (a) antecedents associated with natural resource extraction, which foments the opportunity for illicit activity to thrive; (b) resulting economic, social, and environmental outcomes from illicit activity as it relates to natural resource extraction; and (c) potential moderating processes, which either enable or inhibit illicit activity to occur, including firm‐level tactics that businesses can employ to counteract illicit activity throughout the supply chain and to promote sustainable long‐term operations. An extensive agenda is presented suggesting future research paths, methodologies, theories, and potential contributions.